Cloning and investigation of celery plant Mannose-6-phosphate reductase (M6PR) gene expression in E. coli bacteria to control the catabolism pathway - Abbasali Yadollahi; Ghazal Ghajari (مجله بیوتکنولوژی کشاورزی, 2023)
Objective Compared to other primary photosynthetic products (such as sucrose and starch), little is known about sugar metabolism and how it is integrated with others. Mannose-6-phosphate reductase (M6PR) is a key enzyme involved in mannitol biosynthesis in celery. This study aimed to clone the gene, express and purify the M6PR enzyme and investigate its function on mutated genes in a laboratory environment.